2008
DOI: 10.1021/ja074660g
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Mechanism of Glutathione Reductase for Synthesis of Active Site Bound Metallic Nanoparticles and Electrical Connection to Electrodes

Abstract: It is demonstrated herein that the FAD-dependent enzyme glutathione reductase (GR) catalyzes the NADPH-dependent reduction of AuCl4-, forming gold nanoparticles at the active site that are tightly bound through the catalytic cysteines. The nanoparticles can be removed from the GR active site with thiol reagents such as 2-mercaptoethanol. The deep enzyme active site cavity stabilizes very small metallic clusters and prevents them from aggregating in the absence of capping ligands. The behavior of the GR-nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 32 publications
4
59
2
Order By: Relevance
“…These types of proteins are ubiquitous membrane proteins that facilitate unidirectional substrate translocation across the lipid bilayer by utilizing the energy obtained from the hydrolysis of ATP and have been found to be very diverse with respect to their physiological function and substrate unlike oxidoreductases which mainly catalyse oxidation-reduction reactions coupled to NADP/NAD + utilization [43][44][45]. Subsequent cloning and sequencing of the gene revealed the presence of a disulphide bond (between amino acid 337C and 481C) which confirms the hypothesis of Scott and coworkers [34], implicating an electron shuttle mechanism via a reduced disulphide bridge. This is further supported by the work done by Cason and co-workers [46] who found that reduction of the disulphide bonds resulted in electron transfer to a metal, in their case U(VI).…”
Section: Nanoparticles From Cell-free Extractssupporting
confidence: 74%
See 2 more Smart Citations
“…These types of proteins are ubiquitous membrane proteins that facilitate unidirectional substrate translocation across the lipid bilayer by utilizing the energy obtained from the hydrolysis of ATP and have been found to be very diverse with respect to their physiological function and substrate unlike oxidoreductases which mainly catalyse oxidation-reduction reactions coupled to NADP/NAD + utilization [43][44][45]. Subsequent cloning and sequencing of the gene revealed the presence of a disulphide bond (between amino acid 337C and 481C) which confirms the hypothesis of Scott and coworkers [34], implicating an electron shuttle mechanism via a reduced disulphide bridge. This is further supported by the work done by Cason and co-workers [46] who found that reduction of the disulphide bonds resulted in electron transfer to a metal, in their case U(VI).…”
Section: Nanoparticles From Cell-free Extractssupporting
confidence: 74%
“…This was shown by Cason and co-workers [46] as well as Scott and co-workers [34]. Varying dithionite concentrations revealed that a stoichiometric ratio of less than 1:1 (4.6 μM sodium dithionite to protein) resulted in particles with defined edges.…”
Section: Au(iii): Reductant Ratiomentioning
confidence: 65%
See 1 more Smart Citation
“…36 More recently, electrode surfaces prepared from nanomaterials facilitated protein ET have attracted particular interest due to excellent electrical conductivity, tunable surface chemistry and morphology. 37 Several groups reported that gold nanoparticles (AuNP) and carbon nanotubes (CNT) can serve as electron relays to electrically wire a range of redox proteins (e.g., cytochrome c (Cyt c), 38,39 glucose oxidase (GOD), 40 glutathione reductase, 41 and hydrogenase 23,42 to electrodes. Analogously, "molecular-wire"-like conjugated oligomers were also employed to wire the deeply buried redox site of a copper amine oxidase to a gold electrode.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] GSHR is reported to reduce Au(III) to zerovalent form as well. 20 Thus, the class of pyridine nucleoside dependent oxidoreductases may represent an evolutionarily adaptable platform of inorganic ion reductases, with modifications to the enzyme altering metal ion selectivity. Such a catalytic center, with alterable precursor selectivity, is of interest in biogenic inorganic nanoparticle synthesis.…”
mentioning
confidence: 99%